Early Bone Pain Relief a Reliable Indicator of Successful Para Thyroidectomy - A Comparative Prospective Study - Nazia Haider, Ghansham, Zahid Mahmood, Bilal Burki, Rizwan Karwar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate early bone pain relief as anindicatorof successful Para thyroidectomy in hyperparathyroidism. Methodology: A prospective, comparative study was conducted at the Department of Surgery, Jinnah Postgraduate Medical Center, between March 2022 and August 2022. All patients with symptoms of hyperparathyroidism, confirmed with increased intact parathyroid hormone and elevated levels of calcium onpresentation were included in the study. Patients were classified as primaryhyperparathyroidism when the MIBI scan detected an adenoma with clinical features ofhypercalcemia and increased PTH whereas, patients were diagnosed with secondaryhyperparathyroidism if patient presented with renal failure, persistently high levels of PTH, as well as hypocalcemia. All patients with primary hyperparathyroidism underwentexcision for adenoma while patients with secondary hyperparathyroidism underwenttotal Para thyroidectomy and auto transplantation. Visual analogue scale was used toassess bone pain at presentation and 12 to 24 hours after procedure, and then six-weeks atfollow-up. Change in symptomatology was observed and compared between the twosets of patients. Results: A total of fourteen primary hyperparathyroidism cases were observed in ourcenter. 13 patients presented with bone pain and deformity, three of these patients were operated for renal stones, three patients had depressive symptoms. The calcium ranged from 12-15mg/dl with adenoma ranging from 1.0 cm to 4.0 cm.Three cases were diagnosed as secondary hyperparathyroidism, secondary to renal failure. Total Para thyroidectomy was done to remove all four parathyroid glands with subsequent auto transplant. All patients had hypo calcemic signs postoperative, which was relieved after calcium transfusion for two days followed by oral. Conclusion: In all patients, irrespective of the cause of the hyperparathyroidism, early pain reliefwas correlated with successful parathyroid surgery. Keywords: Parathyroid, hyperparathyroidism, primary, secondary, PTH, calcium, pain